Pemanfaatan Media Sosial Tiktok Terhadap Literasi Religius Siswa Di SMPN 1 Babadan - Sari, Ria Novita; Syahida, Ridha Annisa; Setiyatuti, Rina; Setiani, Ririn; Arfin Yusviyan, Rizya Eka (Social Science Academic, 2024)
Increased use of social media, including the TikTok platform, has become a significant phenomenon among teenagers. On the other hand, religious education and religious literacy are important aspects in forming students' character and morals. However, there has been no in-depth research regarding how the use of TikTok affects students' religious literacy in the school environment, especially at SMPN 1 Babadan. Therefore, this research aims to find out how the use of social media TikTok affects the religious literation of students at SMPN 1 Babadan. This research method uses a qualitative approach with interviews and observations. The research results show that students at SMPN 1 Babadan use TikTok social media for PAI learning such as creating content and searching for material with guidance and supervision from the teacher. The use of social media TikTok can influence the religious literacy of students at SMPN 1 Babadan. This shows the importance of understanding the influence of social media on religious and educational aspects.